Molecular variability among isolates of Mycosphaerella graminicola, the causal agent of septoria tritici blotch, in Argentina - Castillo, Nadia (2010)
The genetic structure and diversity of Mycosphaerella graminicola population were studied with ISSR molecular markers, using isolates from several locations of the Argentinean wheat region: subregion IV (SE of Buenos Aires Province) and II South (central part of Buenos Aires Province). Samples were taken from different bread wheat (Triticum aestivum) cultivars. A total of 126 isolates were subjected to molecular analysis to compare the genetic structure of the isolates from both wheat subregions. Ten ISSR primers were used: (GACA)4; (AAC)7; (ATC)7; (AC)9; (AAG)7; (AG)9; (AGC)5; (CAG)5, (GTG)5 and (GACAC)3. Eighty-four bands ranging from 200 bp to 8.000 were amplified. Eighty-one distinct haplotypes were identified and 43 isolates did not generate any amplification products. The highest number of polymorphic DNA fragments were produced using ISSR primers (ATC)7 and (GTG)5, which detected bands in 38 isolates. The molecular analysis revealed the existence of 81 different haplotypes among the 126 isolates studied. These results revealed a high degree of genetic diversity in the M. graminicola population in Argentina.